Pengaruh Pemanfaatan Layanan E-Mail Billing Tagihan Terhadap Citra PT Pln Batam - Narti Eka Putria (Universitas Putera Batam, 2014)
PT PLN Batam as one of the companies that provide electric power to serve customers in Batam Island and the surrounding areas can not be separated from the competitive climate despite allegedly monopolistic factor is still a force to compel customers to receive services provided by PT PLN Batam. But in fact the competition has taken place in Batam Island, among others, the utilization of electricity for a specific area such as Tunas Industrial Area, Industrial Area Batamindo, and Panbil Industrial Area, and in allowing some companies to manage their own electrical such as Mega Mall, which has a gas plant for its own sake . This shows that competition in the electricity business in Batam has occurred and for the PT PLN Batam should improve service if do not want to be left by customers. The process of sending the bill could use that email can be generated'automatically 'directly to the customer. Means that PT PLN have to create a process that will directly send the bill to the customer when the final email service usage period for example the 1st of each month. In addition to the delivery process (obviously) much faster than the way 'manual', the reduction of paper consumption (and its cost) will be considerably increased. Corporate image is a psychological impression and overview of the various activities of a company in the eyes of the public audience that is based on knowledge, responses and experiences that have been received. Specific assessment of the company's image can be shaped by the public image of good, average and poor.